2016
DOI: 10.1016/j.cemconres.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Discrete element modelling of the fresh state behavior of pervious concrete

Abstract: The objective of this paper is to propose a novel numerical approach to evaluate the fresh state behavior of pervious concrete (PC). A new constitutive law applied to Discrete Element Method was developed for the simulation of the interaction between aggregates connected by fresh cement paste. Several innovative aspects regarding the type of contact model, the consideration of the contact bridge and the inclusion of the rheology coefficients were proposed. A calibration was performed with data from the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 19 publications
2
28
0
2
Order By: Relevance
“…Finally, tests were conducted to evaluate the porosity, density and permeability of mixes. The materials, composition and production process applied here are based on those described by Pieralisi et al [15].…”
Section: Experimental Programmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, tests were conducted to evaluate the porosity, density and permeability of mixes. The materials, composition and production process applied here are based on those described by Pieralisi et al [15].…”
Section: Experimental Programmentioning
confidence: 99%
“…The method proposed by Pieralisi et al [15] was used to simulate the compaction process of pervious concrete. This method takes into account parameters related to the composition of the pervious concrete, like the aggregate grading curve, the P/A ratio and the rheology of the cement paste.…”
Section: Compaction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the accuracy of the established model was satisfied. Pieralisi et al [31] established PC discrete element constitutive law based on cementation between aggregate and cement paste. The effectiveness of the method was verified by the experiments with different aggregate types, grading curves, and aggregate-to-binder ratios.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is important to remark that currently there is no standard to assess the permeability for PC [28]. Concerning that, two types of test are commonly used to measure the permeability coefficient: the falling head permeability test [3,8,10,11,38] and the constant head permeability test [39][40][41][42][43][44].…”
Section: Hydraulic Propertiesmentioning
confidence: 99%